Hydrothermal synthesis, structures and magnetic properties of two new holmium(III) oxalato complexes. Issue 12 (18th June 2017) - Zhang, Yingjie; Karatchevtseva, Inna; Kong, Linggen; Price, Jason R.; Scales, Nicholas; Deen, Stephen; Zheng, Rongkun
Abstract: Two new holmium (Ho) oxalato complexes have been synthesized under hydrothermal conditions and structurally characterized. [Ho(OH)2 ]2 (C2 O4 ) (1 ) has a 3-D structure with Ho-(μ3 -OH) hydroxide layers connected by μ4 -bridging oxalate ligands forming a unique hybrid structure. Sr(H2 O)4 [Ho(C2 O4 )2 (H2 O)]2 ·2H2 O (2 ) has a 3-D structure built through μ2 -bridging oxalate ligands connecting hexagonal Ho oxalate layers with hydrated Sr 2+ ions in the channels. Different oxalate ligand arrangements around the metal ions control the structural alterations among the lanthanoid double oxalates even with similar formulas. Both structures have been discussed and compared to the existing lanthanoid oxalato complexes. In addition, their vibration modes, thermal stabilities, electronic structures, and magnetic properties have been further investigated and reported. Both1 and2 show the deviation of the magnetic behaviors from the Curie–Weiss law due to the crystal field effects. Abstract :